Effect of Placental Cord Blood Drainage on Duration of Third Stage of Labour - Mamoona Javeed, Safia Perveen, Azra Yaseen, Zunaira Bajwa, Nazia Nawaz, Muhammad Suleman Azhar, Fizza Mahmood, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Current study was conducted to explore placental drainage effect on the 3rd stage of labour. Methodology: This randomized controlled clinical trial was directed at normal labour unit at Sahiwal Medical College using non-probability consecutive sampling technique to enroll 112 patients undergoing normal vaginal delivery. Results: This study was conducted from 15th March 2021 till 14th September 2021 after approval of hospital ethical committee. In our study total 112 patients were enrolled and divided in two groups. Mean age of 30.98±4.727 years in PCD group and 32.18±3.298 years in control group. Mean gestational age was 39.187±0.8123 in PCD group and 39.148±0.8123 in control group. Mean pre-delivery hemoglobin levels and hematocrit was also comparable in both groups with p-value more than 0.05. Duration of third stage of labor was significantly shorter in PCD group i.e. 8.53±2.7 minutes as compared to control group i.e. 10.7±5.3 minute, p-value was significant 0.001. There was less blood loss in PCD group, p-value 0.039. post-delivery hematocrit was low in control group, p-value 0.021. There was no relation of age, gender and parity on duration of third stage of labour. Conclusion: Placental Cord Blood Drainage is secure, and effective noninvasive intervention that may help in improving 3rd stage progress.